PENGEMBANGAN LKPD MEMAHAMI TEKS CERPEN BERBASIS DISCOVERY LEARNING UNTUK SISWA KELAS IX SMP - Tria Ardila; Nurlaksana Eko Rusminto; Bambang Riadi (FKIP Universitas Lampung, 2020)
The problem in this study is the development of products in the form of teaching materials LKPD understanding short story text based on the discovery learning for the IX grade students of junior high school. The purpose of this study is to produce teaching materials LKPD understanding short story text based on the discovery learning for the IX grade students of junior high school. This research uses research and development (rnd) method. The result of this study is the creation of a teaching materials LKPD product understanding short story text based on the discovery learning for the IX grade students of junior high school has been validated. Validation is conducted by expert lecturers and practitioners to test the feasibility of the product. The result of the validation is from expert lecturers and practitioners obtained an average percentage of 83% with decent criteria. Masalah dalam penelitian ini adalah bagaimana pengembangan bahan ajar LKPD memahami teks cerpen berbasis discovery learning untuk siswa kelas IX SMP. Tujuan penelitian ini untuk mendeskripsikan pengembangan bahan ajar LKPD memahami teks cerpen berbasis discovery learning untuk siswa kelas IX SMP. Penelitian ini menggunakan metode research and development (rnd).Hasil penelitian ini ialah terciptanya produk LKPD memahami teks cerpen berbasis dicovery learning untuk siswa kelas IX SMP yang sudah divalidasi.Validasi dilakukan oleh dosen ahli dan praktisi untuk menguji kelayakan produk.Hasil validasi dari ahli dan praktisi diperoleh rata-rata persentase 83% dengan kriteria layak.Keywords: teaching materials LKPD, discovery learning, short story text.